2019
DOI: 10.1111/mpp.12885
|View full text |Cite
|
Sign up to set email alerts
|

Ty‐1, a universal resistance gene against geminiviruses that is compromised by co‐replication of a betasatellite

Abstract: Tomato yellow leaf curl virus (TYLCV), a begomovirus, causes large yield losses and breeding for resistance is an effective way to combat this viral disease. The resistance gene Ty-1 codes for an RNA-dependent RNA polymerase and has recently been shown to enhance transcriptional gene silencing of TYLCV. Whereas Ty-1 was earlier shown to also confer resistance to a bipartite begomovirus, here it is shown that Ty-1 is probably generic to all geminiviruses. A tomato Ty-1 introgression line, but also stable transf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…Usually the resulting new disease complexes are characterized by more severe symptoms consisting of extremely stunted and distorted plants ( Figure 4 ) [ 33 , 55 ]. In N. benthamiana , co-replication of TYLCV with ageratum yellow vein betasatellite (AYVB) increases the symptom severity level [ 56 , 57 ]. Co-infection of TYLCMLV and cotton leaf curl Gezira betallatellite (CLCuGB) by cross-feeding of whiteflies resulted in more severe symptoms [ 33 , 54 ].…”
Section: Increasing Global Significance Of Tylcdmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually the resulting new disease complexes are characterized by more severe symptoms consisting of extremely stunted and distorted plants ( Figure 4 ) [ 33 , 55 ]. In N. benthamiana , co-replication of TYLCV with ageratum yellow vein betasatellite (AYVB) increases the symptom severity level [ 56 , 57 ]. Co-infection of TYLCMLV and cotton leaf curl Gezira betallatellite (CLCuGB) by cross-feeding of whiteflies resulted in more severe symptoms [ 33 , 54 ].…”
Section: Increasing Global Significance Of Tylcdmentioning
confidence: 99%
“…Ty-1 confers resistance to TYLCV based on enhanced TGS by increasing cytosine methylation of the viral genome [ 81 ]. Ty-1 -mediated antiviral TGS response has been considered to be generic against geminiviruses as Ty-1 was shown to also confer resistance to a bipartite begomovirus tomato severe rugose virus (ToSRV) [ 81 ] and the leafhopper-transmitted beet curly top virus (BCTV), a curtovirus [ 57 ]. However, co-inoculation with betasatellites expressing the βC1 protein compromises Ty-1 -mediated resistance and induces disease symptoms [ 57 ].…”
Section: Tylcd Control: Mapped Tylcv Resistance Genesmentioning
confidence: 99%
“…Therefore, the Ty -1 gene is representing an entirely new class of disease resistance/tolerance genes that operates by intensifying the levels of transcriptional silencing of viral genes. More recent studies have shown that the Ty -1 gene can also confer resistance to Beet curly top virus (a viral species of the genus Curtovirus ) in genetically transformed Nicotiana benthamiana plants [ 34 ]. However, no information is yet available about the effects of the Ty -1 gene on ssDNA viruses and subviral agents described in association with tomatoes in neotropical areas.…”
Section: Introductionmentioning
confidence: 99%
“…RDR3 from Salvia miltiorrhiza was induced after cucumber mosaic virus (CMV) infection, suggesting its role in the antiviral silencing ( Shao and Lu, 2014 ). Tomato Ty1/Ty3 genes encode for RDRγ and are associated with antiviral resistance ( Voorburg et al, 2020 ). Tomato cultivars with Ty1/Ty3 displayed resistance against begomovirus and tomato yellow leaf curl virus and displayed enhanced viral siRNA (VsiRNA) generation and cytosine methylation of the begomovirus genome.…”
Section: Pathways For Formation Of Transitivity and Their Rolesmentioning
confidence: 99%